Making a life : working by hand and discovering the life you are meant to live - Falick, Melanie (Artisan, a division of Workman Publishing Co., Inc., 2019)
Why do we make things by hand? And why do we make them beautiful? Led by the question of why working with our hands remains vital and valuable in the modern world, author and maker Melanie Falick went on a transformative, inspiring journey. Traveling across continents, she met quilters and potters, weavers and painters, metalsmiths, printmakers, woodworkers, and more, and uncovered truths that have been speaking to us for millennia yet feel urgently relevant today: We make in order to slow down. To connect with others. To express ideas and emotions, feel competent, create something tangible and long-lasting. And to feed the soul. In revealing stories and gorgeous original photographs, Making a Life captures all the joy of making and the power it has to give our lives authenticity and meaning. --Provided by publisher.